A comparison of the 'old' and 'new' literature components: teachers' perception / Nasuha Suhaili - Suhaili, Nasuha (Faculty of Education, 2010)
This study attempts to find out the perception of teachers' towards the 'old' and 'new' literature components in the English Language syllabus in the Melaka Tengah district area. It also aims to identify the relationship between respondents' background information and their classroom practices. To carry out this study, a questionnaire consisting of 65 items was used. The questionnaire was designed to obtain information regarding their demographic and educational background and more importantly their perceptions on the 'old' and 'new' literature components. The 5-point Likert scale was used to gauge teachers' perceptions. The participants were teachers teaching the literature component in Form One and Form Four from ten schools in the district of Melaka Tengah. Data were analysed using frequency counts while a cross sectional study on teachers' classroom practices were carried out using Analysis of Variance (ANOVA). The findings revealed that teachers who are better qualified and experienced carry out positive classroom practices. The findings also revealed the suitability of the literature texts of the 'old' and 'new' literature component in terms of students' proficiency, maturity level, cultural background and interest. Pedagogical implications such as increase training for English teachers as those who are trained rely less on the training module, the success for the teaching and learning of literature relies on the choice of text based on students' language proficiency, maturity level and cultural background and that the teaching material created should consider its impact on students' literacy skills, interest in reading and promoting classroom participation.